Direct Control of a Computer Cursor by Frontal Cortical Ensembles in Humans: Prospects for Neural Prosthetic Control - Donoghue, J.P.; Saleh, M.; Caplan, A.; Serruya, M.D.; Morris, Dan; Ramchandani, S.; Ojakangas, C. (Society for Neuroscience Annual Meeting, November 2003, 2003)
Neural prosthetic devices for paralyzed patients based on implanted microelectrode arrays will require humans to use neural output to control devices. Previously we demonstrated that nonhuman primates could substitute the decoded output of motor cortex neurons for hand motion to perform visuomotor tasks (Serruya et al., 2002 Nature 416:141). As a next step we are examining whether cortical ensembles can be used in humans to achieve rapid, accurate control of external devices. Multielectrode recordings were performed intraoperatively in the premotor/prefrontal cortex of patients prior to mapping for implantation of a deep brain stimulator to treat movement disorders. Patients were mildly sedated, but sufficiently alert to participate in visually-guided arm movement tasks. Participants performed either a 4 direction center out task or a random-target step tracking task using planar arm movements; hand position and targets were displayed on a video monitor. A depth electrode system (5 electrode array) was introduced into the premotor/prefrontal cortex at the site where the DBS implant track was located. Up to 9 neurons have been simultaneously recorded in two patients. Tasks were performed either with hand or neural control of the position feedback cursor. The neural cursor was driven from a linear weighted sum of neural spiking, with filter coefficients determined from a few minutes of spiking during hand control. Patients tested so far could move the neural cursor towards targets, despite ambiguity in the recording location and the small number of neurons available. One patient reached the targets in 13/16 attempts lasting < 5 sec each. These findings suggest that small populations of frontal cortex neurons can be used to control devices in humans.